2014
DOI: 10.3892/ol.2014.2772
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 polymorphism in breast cancer patients from Argentina

Abstract: Breast cancer is the most common type of cancer in females in Argentina, with an incidence rate similar to that in the USA. However, the contribution of the BRCA1 or BRCA2 mutation in breast cancer incidence has not yet been investigated in Argentina. In order to evaluate which BRCA1 polymorphisms or mutations characterize female breast cancer in Argentina, the current study enrolled 206 females with breast cancer from several hospitals from the southeast of Argentina. A buccal smear sample was obtained in dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…VUSs in BRCA1 are a type of variants whose functions in protein level are yet to be survived. However, BRCA1 polymorphisms may affect protein, causing it to lose function, and thereby to increase the risk of developing breast cancer (6).…”
Section: Introductionmentioning
confidence: 99%
“…VUSs in BRCA1 are a type of variants whose functions in protein level are yet to be survived. However, BRCA1 polymorphisms may affect protein, causing it to lose function, and thereby to increase the risk of developing breast cancer (6).…”
Section: Introductionmentioning
confidence: 99%
“…We have found sequences reported as polymorphic at both BRCA1 and BRCA2 , presumably with no pathogenic effect (Domchek and Greenberg ; Jaure et al. ) (Table ). Many BRCA1 single nucleotide polymorphisms (SNPs) result in amino acid changes.…”
Section: Discussionmentioning
confidence: 84%
“…Chakraborty et al also confirmed the absence of mutation by Sanger sequencing 8 . Only family positive cases were selected because inherited mutations in high penetrance BRCA genes closely correlated with an increased risk of breast cancer in different ethnic and age groups 14 .…”
Section: Discussionmentioning
confidence: 99%